Rapid assessment of physical activity score in maintenance hemodialysis patients with nutritional assessment - Vinitha Varghese; Madhusudan Vijayan; Georgi Abraham; Sam Nishanth; Milly Mathew; Rajeevalochana Parthasarathy; Nevin Mancha (Society of Diabetic Nephropathy Prevention, 2019)
Introduction: There is a paucity of data from India regarding the physical activity assessment of hemodialysis patients. Objectives: The objective of this study was to determine the level of physical activity and nutritional status of Indian dialysis patients. Patients and Methods: This cross-sectional multicenter study was conducted in two tertiary care centers. The physical activity of 116 patients was assessed by the Rapid Assessment of Physical Activity (RAPA) questionnaire and correlated with various biochemical parameters of nutrition. Results: We divided the patients based on serum albumin level into group 1 (≤ 3.5 g/dL) and group 2 (>3.5 g/dL). The mean RAPA-1 scores of both groups were suboptimal; group 1 had a mean score of 2.514 ± 0.901 and group 2 had a mean score of 3.215 ± 1.257 (P=0.003). The mean handgrip strength of group 1 was 35.222 ± 13.568 kg and that of group 2 was 41.472 ± 17.874 kg (P=0.062). Conclusion: These results should alert physicians taking care of maintenance hemodialysis patients to improve nutritional status and thereby physical activity to ensure better outcomes.